The Effect of Guided Inquiry Learning Model on Improving Students' Learning Outcomes and Science Process Skills on Chemical Bonding Materials - Serli Margarettha Ginting; Anna Juniar (Jurnal Pendidikan dan Pembelajaran Kimia, 2022)
Abstract: The Effect of Guided Inquiry on Improving Learning Outcomes and Science Process Skills of Students on Chemical Bonding. This study aims to determine the effect of the guided inquiry learning model on student learning outcomes and science process skilss and its correlation to chemical bonding material. The research method used is quasi-experimental. This research was conducted at SMA Negeri 1 Berastagi. The sample of this study consisted of two classes, namely the experimental class which was taught using the guided inquiry model and the control class which was taught using the conventional learning model, each class consisted of 30 students. The instruments used are multiple choice tests (study outcomes), essay tests (science process skills), student worksheets and observation sheets on the implementation of science process skills. In this study, the data that was processed was the value of learning outcomes gain and science process skills of students in both classes. Data analysis was processed in the SPSS 21 application for windows. The data analysis technique used is analysis using the Independent Sample T-Test and to calculate the correlation, multiple correlation tests are used. The results showed that there was an influence of the guided inquiry learning model on student learning outcomes and science process skills and there was a significant correlation between student learning outcomes and student science process skills through the application of the guided inquiry learning model.Keywords: Guided Inquiry, Learning Outcomes, Student Science Process Skills, Chemical BondsAbstrak: Pengaruh Pembelajaran Inkuiri Terbimbing terhadap Peningkatan Hasil Belajar dan Keterampilan Proses Sains Siswa pada Materi Ikatan Kimia. Penelitian ini bertujuan untuk mengetahui pengaruh model pembelajaran inkuiri terbimbing terhadap hasil belajar dan keterampilan proses sains siswa serta korelasinya pada materi ikatan kimia. Metode penelitian yang digunakan adalah kuasi experimen. Penelitian ini dilaksanakan di SMA Negeri 1 Berastagi. Sampel dari penelitian ini terdiri dari dua kelas yaitu kelas eksperimen yang dibelajarkan menggunakan model inkuiri terbimbing dan kelas kontrol yang dibelajarkan dengan model pembelajaran konvensional, masing-masing kelas berjumlah 30 siswa. Instrumen yang digunakan berupa tes pilihan ganda (hasil belajar), tes esai (keterampilan proses sains), lembar kerja peserta didik dan lembar observasi keterlaksanaan keterampilan proses sains). Dalam penelitian ini data yang diolah adalah nilai gain hasil belajar dan KPS siswa kedua kelas. Data dianalisis diolah menggunakan uji Independent Sample T-Test dan uji korelasi berganti menggunakan SPSS 21. Hasil penelitian menunjukkan bahwa terdapat pengaruh model pembelajaran inkuiri terbinbing terhadap hasil belajar dan KPS siswa serta terdapat korelasi yang signifikan antara hasil belajar dan KPS siswa melalui penerapan model pembelajaran inkuiri terbimbing.Kata kunci: Inkuiri Terbimbing, Hasil Belajar, Ketdrampilan Proses Sains Siswa, Ikatan Kimia DOI: http://dx.doi.org/10.23960/jppk.v11.i1.2022.09